Analisis Informasi Citra Anatomi Fase Late Artery dengan Variasi Time Scan Delay pada Pemeriksaan MSCT Abdomen - Bagus Abimanyu; Luthfi Rusyadi; Taufiq Taufiq (Jurnal Imejing Diagnostik (JImeD), 2017)
Background: MSCT Abdomen late arterial phase is a radiological examination to evaluated enhancement in hypervascular lesions, stomach, bowel, pancreas parenchyma, spleen and kidney outer cortex. All the structures get bloodsupply of the artery will show an optimal increase (Smithuis, 2014). Smithuis (2014) used time scan delay 15-20 seconds. However in the Abdomen MSCT examination in the late arterial phase of Radiology Hospital Dr. Kanujoso Djatiwibowo Balikpapan used  the different time scan delay. This study aimed to determine differences in contrast enhancement with time scan delay variation of contrast media and to determine the optimal time scan delay in the examination of the Abdomen  MSCT late arterial phase.Methods: The research type is quantitative experimental approach. Data are taken in October and November 2016. The research population of abdomen MSCT examination clinical intra-abdominal mass cases. Total sample are 18 people with a predetermined inclusion criteria. Time scan delay variation used  are 10 seconds, 15 seconds, 20 seconds. evaluated with  respondents the  data is processed with statistic analysis by using different test Kruskal-Wallis followed by post hock Mann-Whitney and to get the most optimal assessment visits of mean rank the Kruskal-Wallis test.Result: The results obtained p value 0,001 (p 0,05), there are  shown significant differences between time scan delay 10 seconds, 15 seconds, 20 seconds at Abdomen  MSCT examination in the late arterial phase of Radiology Dr. Kanujoso Djatiwibowo Balikpapan Hospital. An optimal time scan delay on Abdomen MSCT examination late arterial phase is 10 seconds premises ROI tracking on descenden aorta. From the results of tests conducted using the Kruskal-Wallis test values mean rank at the time scan delay of 10 seconds is 84,75.Conclusison: There is a difference significant anatomical image information between the time scan delay 10 seconds, 15 seconds, 20 seconds. on MSCT Abdomen examination artery in the late phase of Radiology  Dr. Kanujoso Djatiwibowo Balikpapan Hospital. assessment results are tested using the Kruskal-Wallis test followed Mann-Whitney post hock obtained p value 0.001 (p 0.05), meaning that there is a difference between the third anatomical image information  with time scan delay variations. Time delay optimal scan on  Abdomen MSCT examination late artery phase that time scan delay 10 seconds by tracking ROI on descenden aorta. From the results of tests conducted using the Kruskal-Wallis test values mean rank at the time scan delay of 10 seconds 84.75, 56.62 ie 15 seconds, 20 seconds, namely 22.12.